PEDAGOGICAL BASES OF DEVELOPMENT OF CREATIVE ABILITIES OF TEACHERS IN FINE ARTS CLASSES - Kalliklishov Sharafadin Orazovich; Bekmuratov Talgat Ubaidullaevich (PEDAGOGS, 2024)
Abstract: The role of teachers in visual arts education goes beyond imparting technical skills and knowledge; it includes fostering creativity, fostering artistic expression, and fostering a lifelong passion for the arts. Teachers play an important role in the formation of creative abilities of students as pedagogues in the field of visual arts. However, in order to effectively develop creativity in students, teachers themselves must embody and develop creative abilities. This article explores pedagogical principles aimed at developing teachers' creative abilities in visual arts classes.